A comparative study of centralised and decentralised architectures for network traffic control. Issue 5 (4th July 2019) - Sha, Rui; Chow, Andy H. F.
ABSTRACT: This paper presents a comparative study of centralised and decentralised architectures for managing urban road network efficiency with consideration of users' responses and uncertainties with respect to prevailing traffic conditions. The control systems are applied to different network topologies with different levels and spatial distributions of traffic demand. The study reveals that the computationally effective decentralised systems could perform almost as well as the conventional centralised one when users' responses are taken into account with provision of real-time traffic information. This generates new insight on cooperative transport management with applications of information and communication technology.